Challenges and opportunities for smallholder livestock production in post-conflict South Kivu, eastern DR Congo - Maass, Brigitte L.; Katunga Musale, Dieudonné; Chiuri, Wanjiku L.; Gassner, Anja; Peters, Michael (Springer, 2012)
A survey on smallholder livestock production with emphasis on monogastric animals was conducted in 20 villages of seven so-called ‘groupements’ of South Kivu province in DR Congo, situated along a north to south-west axis with the town of Bukavu in the center. This land adjacent to Lake Kivu is located at elevations ranging around 900–1900 m asl, experiencing tropical highland climate. A diagnostic survey helped to rapidly obtain in-depth knowledge of constraints and opportunities in this environment. Correspondence analysis and multiple regression analysis were used to investigate the association of production constraints with particular livestock species and to understand the factors that govern the number of livestock that people owned (converted to tropical livestock units [TLU]), respectively. Responses of 112 informants demonstrated that livestock is an integral part of the region’s mixed farming systems. Low livestock numbers per household at present reflect the poverty as a consequence of recent violent conflicts. Currently, farmers focus on small livestock, like poultry, swine, cavies (i.e., Guinea pigs) and rabbits. Families keep livestock to accumulate household reserves that are strongly invested in children’s education. Major issues of animal husbandry were related to animal diseases and lack of feed resources, particularly in the dry season. Lack of feed or forages were unrelated to a particular livestock species. Livestock holdings depended on animal diversity, location, land size available and respondents’ education level. The potential introduction of improved forages is challenged by their dry-season tolerance, compatibility with cropping on small farms; and people’s readiness to cultivate forages.